Saudi-Iran conflict: challenges beyond Sunni-Shia tensions - Saleem, Saleena (2016)
Saudi Arabia’s latest moves that precipitated the recent escalation in Sunni-Shiite sectarian tension in the Middle East are indicative of its sense of vulnerability about its mounting challenges as Iran normalises relations with the international community.